Learning approaches in university students from Buenos Aires - Freiberg Hoffmann, Agustín; Fernández Liporace, Mercedes; Ledesma, Rubén (Pensando Psicología, 2017)
Introduction: Learning approaches allude to the predisposition to learn in different academic situations. Objective: These approaches (deep and superficial) are analyzed in university students from Buenos Aires. Methodology: 397 students between 18 and 36 years old from different schools (Exact and Natural Sciences, Psychology, Engineering, Law, and Medicine) participated. Results: The results showed differences according to sex in deep and superficial approaches, favorable to women in the first case, and to men in the second. With respect to the School variable, several differences were recorded in which Exact and Natural Sciences students stood out in the deep approach, and Engineering students in the superficial, in relation to the rest of schools. Subsequently, the relationship between approaches and academic performance in each school was analyzed, corroborating statistically significant associations for the Engineering and Medicine groups. Conclusions: Results show the effect that the School variable has on learning approaches, accounting for the relevance that teaching types have in shaping them. The observed correlations with academic performance highlight the importance of the type of approach for certain programs. It is expected that the information presented contributes to the planning of activities tending to improve students’ learning of contents.